IP routing - Malhotra, Ravi (O'Reilly, 2002)
"This book introduces the reader to the intricacies of IP routing as it is implemented using Cisco routers. Each section leads the reader through the basics of configuring routing protocols. This approach gives the reader a quick start with the routing protocol under discussion and reveals the underlying concepts of IP routing. What is the packet-forwarding process? How is the routing table maintained? How do Distance Vector algorithms work? How do classful and classless route lookups differ? These and other concepts are illustrated in the discussion of static routing, RIP, IGRP and EILGRP. The limitations of these traditional routing protocols will also become obvious to the reader. Variable Length Subnet Masks, route sumamrization, and fast convergence are key features in the design of any large IP network. These features are discussed in the OPSF chapter, which includes an introduction to Dijkstra's algorithm, the foundation of Link State protocols. Finally, BGP-4 is described in detail, showing the reader how to use BGP-4 attributes to set routing policies."--Back cover.